A systematic review of propulsion from the flutter kick - What can we learn from the dolphin kick - Andersen, J. T.; Sanders, R. H. (Journal of Sports Sciences, 2018)
Propulsion, one of the most important factors in front crawl swimming performance, is generated from both the upper and lower limbs, yet little is known about the mechanisms of propulsion from the alternating movements of the lower limbs in the flutter kick (FK). The purpose of this systematic review was to review the literature relating to the mechanisms of propulsion from FK in front crawl. There was limited information about the mechanisms of propulsion in FK. Since movements of the lower limbs are similar between FK and the dolphin kick (DK), mechanisms of propulsion from DK were reviewed to better understand propulsion from FK. Recent evidence suggests that propulsion in DK is generated in conjunction with formation and shedding of vortices. Similar vortex structures have been observed in FK. Visualisation and simulation techniques, such as particle image velocimetry (PIV) and computational fluid dynamics (CFD), are non-invasive tools that can effectively model water flow without impacting swimming technique. These technologies allow researchers to estimate the acceleration of water and, consequently, the propulsive reaction forces acting on the swimmer. Future research should use these technologies to investigate propulsion from FK.